Exploring the Directives of Communicability for Improving the Quality of Software Artifacts - Lopes, Adriana; Conte, Tayana; de Souza, Clarisse Sieckenius (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2020)
Software artifacts developed in the early stages of the development process describe the proposed solutions for the software in construction. Thus, these artifacts support team communication. Failures in communication via software artifacts occur because practitioners typically concentrate on the artifacts’ content, without reflecting on how other software development team members will interpret these artifacts. Such communication failures can negatively affect the quality of software artifacts. To support better communication via artifact, we proposed the Directives of Communicability (DCs). The DCs aim to support practitioners in analyzing the characteristics that affect the artifacts’ content on team communication. In this paper, we present an exploratory study carried out to evaluate the practitioners’ perception about the contribution of DCs to the quality of a specific software artifact. The results indicate that DCs contribute to this purpose. We noticed positive perceptions of practitioners about the use of DCs in software artifacts.